Immortalization and functional screening of natively paired human T cell receptor repertoires. (17th February 2022) - Fahad, Ahmed S; Chung, Cheng-Yu; Lopez Acevedo, Sheila N; Boyle, Nicoleen; Madan, Bharat; Gutiérrez-González, Matias F; Matus-Nicodemos, Rodrigo; Laflin, Amy D; Ladi, Rukmini R; Zhou, John; Wolfe, Jacy; Llewellyn-Lacey, Sian; et al.
Abstract: Functional analyses of the T cell receptor (TCR) landscape can reveal critical information about protection from disease and molecular responses to vaccines. However, it has proven difficult to combine advanced next-generation sequencing technologies with methods to decode the peptide-major histocompatibility complex (pMHC) specificity of individual TCRs. We developed a new high-throughput approach to enable repertoire-scale functional evaluations of natively paired TCRs. In particular, we leveraged the immortalized nature of physically linked TCRα:β amplicon libraries to analyze binding against multiple recombinant pMHCs on a repertoire scale, and to exemplify the utility of this approach, we also performed affinity-based functional mapping in conjunction with quantitative next-generation sequencing to track antigen-specific TCRs. These data successfully validated a new immortalization and screening platform to facilitate detailed molecular analyses of disease-relevant antigen interactions with human TCRs.